HIV-1 infection in high risk men who have sex with men in Mombasa, Kenya. - Sanders, E; Graham, S; Okuku, H; van der Elst, E; Muhaari, A; Davies, A; Peshu, N; Price, M; McClelland, R; Smith, A (2007)
BACKGROUND: The role of homosexuality and anal sex practices in the African HIV -1 epidemic is not well described. We aimed to assess the risk factors for prevalent HIV-1 infection among men who have sex with men (MSM) to guide HIV-1 prevention efforts. METHODS: Socio-behavioural characteristics, signs and symptoms of sexually transmitted diseases (STD), and serological evidence of HIV-1 were determined for 285 MSM at enrolment into a vaccine preparedness cohort study. We used multivariate logistic regression to assess risk factors for prevalent HIV-1 infection. RESULTS: HIV-1 prevalence was 43.0% [49/114, 95% confidence interval (CI), 34-52%] for men who reported sex with men exclusively (MSME), and 12.3% (21/171, 95% CI, 7-17%) for men who reported sex with both men and women (MSMW). Eighty-six (75%) MSME and 69 (40%) MSMW reported recent receptive anal sex. Among 174 MSM sexually active in the last week, 44% reported no use of condoms with casual partners. In the previous 3 months, 210 MSM (74%) reported payment for sex, and most clients (93%) were local residents. Prevalent HIV-1 infection was associated with recent receptive anal sex [odds ratio (OR), 6.1; 95% CI, 2.4-16], exclusive sex with men (OR, 6.3; 95% CI, 2.3-17), and increasing age (OR, 1.1 per year; 95% CI, 1.04-1.12). Only four MSM reported injecting drug use. CONCLUSIONS: The high prevalence of HIV-1 in Kenyan MSM is probably attributable to unprotected receptive anal sex. There is an urgent need for HIV-1 prevention programmes to deliver targeted risk-reduction interventions and STD services to MSM in Kenya.